The third pillar in Europe: institutional factors and individual decisions - Julia Le Blanc (Deutsche Bundesbank, 2011)
This paper studies and documents household participation in voluntary individual retirement accounts (IRAs) in eleven European countries. Using recently available, internationally comparable data of households aged 50+, we calculate country-by-country average marginal effects of the probability to save in IRAs. We link the evidence from the micro data to the institutional differences in pension systems that prevail across the countries in our sample. Our results indicate that households' participation in the 'third pillar' varies substantially across countries, both due to institutional differences and household characteristics. Higher education is crucial for participation in countries with shorter traditions of IRAs where awareness matters most. Background risk due to expectations of future pension reforms as well as experience with occupational pensions increase voluntary retirement savings additionally for the currently employed individuals in our sample.
Keywords: D12; G11; J26; 330; individual retirement accounts; pension reform; consumption and saving over the life-cycle